THE MANY FACES OF SCHOOL VIOLENCE - Cezar da Silva Neto, Olimpio (Revista Gênero e Interdisciplinaridade, 2023)
The main objective of this research is to carry out a bibliographical analysis on the subject of school violence in the daily life of educational institutions. With this, it is clear that it is a worldwide phenomenon. Events not only increased, but also diversified, bringing to light other forms and means of manifestation such as cyberbullying, for example. Likewise, new modalities and different types of behavior are suggested. In these terms, it is essential to develop strategies that are useful both in eradicating and, above all, in preventing any type of school violence, as this and bullying end up affecting students and future citizens. It is concluded that school violence is a phenomenon that exists in the school environment, which involves the whole society and it is possible to mitigate it with good strategies.